Exosome-Derived Non-Coding RNAs in the Tumor Microenvironment of Colorectal Cancer: Possible Functions, Mechanisms and Clinical Applications - Chen, Xian; Jia, Mengmeng; Ji, Jing; Zhao, Zhiying; Zhao, Yanjie (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is the second leading cause of cancer death and the third most prevalent malignancy. Colorectal tumors exchange information with the surrounding environment and influence each other, which collectively constitutes the tumor microenvironment (TME) of CRC. Many studies have shown that exosome-derived non-coding RNAs (ncRNAs) play important roles in various pathophysiological processes by regulating the TME of CRC. This review summarizes recent findings on the fundamental roles of exosomal ncRNAs in angiogenesis, vascular permeability, tumor immunity, tumor metabolism and drug resistance. Certainly, the in-depth understanding of exosomal ncRNAs will provide comprehensive insights into the clinical application of these molecules against CRC.